Comparative analysis of weld strength of nickel-chromium and cobalt-chromium base metal alloys when submitted to tungsten inert gas welding - Amrutha Shenoy; Nabeel Ahmed; Vaishnavi Rajaraman; Subhabrata Maiti; Dhanraj M Ganapathy (Wolters Kluwer Medknow Publications, 2022)
Long span base metal alloy fixed prosthesis and partial dental prosthesis frameworks most often require welding for better fit and adaptation. The type of metal alloys used and its effect on the weld strength of the prosthesis have to be investigated. The aim of the study is to comparatively analyze the weld strength of nickel-chromium (Ni-Cr) and cobalt-chromium (Co-Cr) base metal alloys when subjected to tungsten inert gas (TIG) welding. 10 nickel- and cobalt-based specimens were obtained by casting of castable resin patterns of dimension 25 mm × 3 mm × 1 mm. Welding of the samples was carried out using the Lampert PuK 2 welding equipment, and a three-point bend test using a universal testing machine was carried out to evaluate the weld strength of the specimens. Statistical analysis was carried out using the SPSS software version 23. Higher weld strength was observed in the Co-Cr alloy (mean = 898 MPa) than in the Ni-Cr alloy (mean = 690 MPa), when submitted to TIG welding (P < 0.05). TIG welding could be a better alternative for joining base metal alloys for long span edentulous cases, and cobalt-based alloys could be better alternatives to nickel-based alloys that usually tend to cause hypersensitivity reactions.